2008
DOI: 10.1128/iai.01396-07
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of the Whole Secretome of Legionella pneumophila and Functional Analysis of Outer Membrane Vesicles

Abstract: Secretion of effector molecules is one of the major mechanisms by which the intracellular human pathogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
166
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(170 citation statements)
references
References 81 publications
4
166
0
Order By: Relevance
“…Seventy percent of our quantified extracellular proteome (54 of 77 proteins) is covered by the secretome data of Galka et al, which is a reasonable overlap and therefore, presence of nonclassically secreted proteins may at least in part be explained by budded outer membrane vesicles. Indeed, eight of the extr in our study which were predicted as periplasmic or membranebound were previously identified in outer membrane vesicles (28). Moreover, six of the predicted 14 cytoplasmic, seven of the 11 predicted membrane, and 14 of the 21 predicted periplasmic proteins in our study were previously identified as L. pneumophila extracellular proteins (28).…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 86%
See 3 more Smart Citations
“…Seventy percent of our quantified extracellular proteome (54 of 77 proteins) is covered by the secretome data of Galka et al, which is a reasonable overlap and therefore, presence of nonclassically secreted proteins may at least in part be explained by budded outer membrane vesicles. Indeed, eight of the extr in our study which were predicted as periplasmic or membranebound were previously identified in outer membrane vesicles (28). Moreover, six of the predicted 14 cytoplasmic, seven of the 11 predicted membrane, and 14 of the 21 predicted periplasmic proteins in our study were previously identified as L. pneumophila extracellular proteins (28).…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 86%
“…Nevertheless, the here presented extracellular proteome contained a subset of proteins which, based on predictions, were unlikely candidates for classic secretion. However, L. pneumophila is known to shed outer membrane vesicles from intact membranes during intra-and extracellular growth (28). The study by Galka et al analyzed proteins found in outer membrane vesicles expelled by L. pneumophila and culture supernatants devoid of them (28).…”
Section: Overview Of L Pneumophila E and Pe Soluble Whole Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…T2S substrates move across the inner membrane via the Sec or Tat pathway and then a pseudopilus acts to push the proteins through an outer membrane pore (Korotkov et al, 2012). Based upon examination of the virulent strain 130b, L. pneumophila T2S exports ¢25 proteins, including 18 confirmed enzymes (Cianciotto, 2009;DebRoy et al, 2006a, b;Galka et al, 2008;Herrmann et al, 2011;Pearce & Cianciotto, 2009;Tyson et al, 2013). L. pneumophila mutants lacking the T2S apparatus are greatly impaired for infection of Acanthamoeba castellanii, Hartmannella vermiformis and Naegleria lovaniensis (Hales & Shuman, 1999;Liles et al, 1999;Polesky et al, 2001;Rossier & Cianciotto, 2001, 2005Rossier et al, 2004Rossier et al, , 2008Tyson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%